NeoBeat offers rapid newborn heart rate assessment. Issue 5 (21st January 2021) - Bush, Jessica Brittany; Cooley, Victoria; Perlman, Jeffrey; Chang, Catherine
Abstract : Background: Heart rate (HR) is used to guide interventions during delivery room (DR) neonatal resuscitation. Dry electrode ECG (NeoBeat) may detect HR more rapidly than pulse oximetry (PO) and portable ECG, but real-time comparisons of these devices are lacking. Design/methods: PO, ECG and NeoBeat were placed sequentially on newborns in the DR. Time for device placement and time to accurate HR acquisition were noted. Results: DR resuscitations of 28 preterm/term infants were observed. The NeoBeat was placed faster (ie, 3 s) than PO (20 s, p=<0.0001) and ECG (16 s, p=<0.0001). Total time from initiation of device placement to HR acquisition was fastest with NeoBeat (13 s) versus ECG (42 s, p<0.0001) and PO (105 s, p<0.0001) (duration values=median). Conclusions: These observations in a small cohort of relatively well neonates demonstrate that the NeoBeat is significantly faster to place and consistently acquires HR faster than PO and ECG. Abstract : This observational study of 28 relatively well newborn infants conducted in the delivery room demonstrated that a novel dry electrode ECG, the NeoBeat, displayed heart rate more quickly than conventional ECG or pulse oximetry.